Adoption of Berastagi Verse in Mobile Metaverse Learning: Extending TAM With Immersion and Cultural Value - Rian Farta Wijaya; Randi Rian Putra (Yayasan Riset dan Pengembangan Intelektual (YRPI), 2026)
This study examines user acceptance of Berastagi Verse, a Roblox-based mobile metaverse learning platform that reconstructs tourism destinations in Berastagi, Indonesia, for cultural learning. The study extends the Technology Acceptance Model by adding immersive experience and cultural value as predictors of behavioral intention. A purposive sample of 180 respondents who used the platform on smartphones completed a questionnaire after interacting with the system. Data were analyzed using PLS-SEM. Perceived ease of use positively influenced perceived usefulness, and both constructs positively predicted behavioral intention. Immersive experience and cultural value also had significant direct effects on intention. The model explained 64.2% of the variance in behavioral intention, suggesting meaningful explanatory power for this context. The findings indicate that mobile metaverse learning is adopted not only for usability and usefulness, but also for the extent to which it feels immersive and culturally relevant. For educational designers, the results suggest that mobile learning platforms should combine intuitive interaction, clear pedagogical value, and culturally authentic content when seeking user adoption.